ANALISIS FAKTOR KINERJA PENGISIAN DOKUMEN REKAM MEDIS RAWAT INAP KLINIK dr. M. SUHERMAN JEMBER - Aditya Dwi Arimbi; Selvia Juwita Swari; Novita Nuraini; Indah Muflihatin; Gamasiano Alfiansyah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Percentage of incompleteness of filling in the medical records of the Clinic Dr. M. Suherman shows thatthe Minimum Service Standards in the Hospital are not yet 100%. Incomplete data has shown that thecompleteness of filling medical record documents is still not in accordance with the specified standards.The incompleteness of filling out the medical record document may be caused by the performance factorof the officer in completing the inpatient medical record document. The purpose of this study is to analyzethe performance factors in filling out the record documents. The purpose of this study was to analyze theperformance factors in filling out medical records of inpatients at the Clinic dr. M. Suherman Jember. Thisstudy uses qualitative research that aims to identify and analyze performance factors in filling inpatientmedical record documents at the Clinic dr. M. Suherman Jember, who will be associated with performancetheory with personal factors, leadership factors, team factors, system factors, and situational factors, andusing the USG (Urgency, Seriousness, Growth) method to determine the main factors of the 5 factors thataffect performance as well as efforts to correct problems using brainstorming. The results of this studyobtained priority causes of the incompleteness of filling medical records documents for inpatients at theClinic dr. M. Suherman Jember is the lack of awareness of each individual related to filling medical recorddocuments, lack of evaluation and monitoring, lack of socialization, lack of understanding related to SOPfor filling medical record documents because there is no SOP for filling medical record documents, so theClinic, Dr. M. Suherman asked researchers to make SOPs for filling in the records of inpatients. As asuggestion, do a commitment to complete the completeness of filling medical record documents, conductsocialization, evaluation and routine monitoring, as well as making SOP for filling medical recorddocuments.